Effects of Intra-session Exercise Sequence during Water-based Concurrent Training - Pinto, S. S.; Cadore, E. L.; Alberton, C. L.; Zaffari, P.; Bagatini, N. C.; Baroni, B. M.; Radaelli, R.; Lanferdini, F. J.; Colado, J. C.; Pinto, R. S.; Vaz, M. A.; Bottaro, M.; Kruel, L.F. M. (International Journal of Sports Medicine, 2014)
The aim was to investigate the effects of the intra-session exercise order during water-based concurrent training on the neuromuscular adaptations in young women. 26 women (25.1±2.9 years) were placed into 2 groups: resistance prior to (RA) or after (AR) aerobic training. Subjects performed resistance (sets at maximal effort) and aerobic training (exercises at heart rate corresponding to the second ventilatory threshold) twice a week over 12 weeks, performing both exercise types in the same training session. Upper (elbow flexion) and lower-body (knee extension) one-repetition maximum test (1RM) and peak torque (PT) were evaluated. The muscle thickness (MT) of upper (sum of MT of biceps brachii and brachialis) and lower-body (sum of MT of vastus lateralis, vastus medialis, vastus intermedius, and rectus femoris) was determined by ultrasonography. Moreover, the maximal electromyographic activity (EMG) of upper (biceps brachii) and lower-body (sum of EMG of vastus lateralis and rectus femoris) was measured. Both RA and AR groups increased the upper and lower-body 1RM and PT, while the lower-body 1RM increases observed in the RA was greater than AR (43.58±14.00 vs. 27.01±18.05%). RA and AR showed MT increases in all muscles evaluated, while the lower-body MT increases observed in the RA were also greater than AR (10.24±3.11 vs. 5.76±1.88%). There were increases in the maximal EMG of upper and lower-body in both RA and AR, with no differences between groups. Performing resistance prior to aerobic exercise during water-based concurrent training seems to optimize the lower-body strength and hypertrophy.
Keywords: maximal dynamic strength; isometric peak torque; muscle thickness; electromyography; resistance exercise; aerobic exercise